Teachers’ Perceptions Toward The Use of English Textbook - M.R, Elvira Rosyida (Universitas Islam Negeri Raden Intan Lampung, 2016)
This study is aimed at: (1) investigating teachers’ perceptions toward the use of English textbook; (2) identifying factors that affect teachers’ perceptions toward the use of English textbook; (3) investigating teachers’ experience in selecting, analyzing, organizing, interpreting, and integrating English textbook; and (4) identifying problems arising while the teachers select, analyze, organize, interpret, and integrate English textbook. This study was conducted with two English teachers of twelfth grade of State Senior High School 3 Surakarta, Jawa Tengah. The data were taken from questionnaire, semi-structured interview, and non-participant observation. The data were analyzed by using Interactive Model. The findings showed that: (1) The teachers believe that they have to consider some considerations to check what is actually contained in the textbook. They do not always follow all the sequences of the materials and activities suggested by the textbook author, but based on the students’ needs. They reveal that textbooks should go hand in hand with supplementary teaching materials to serve students’ needs even though they are relatively satisfied with the textbook choice; (2) Their perceptions are influenced by some factors such as experience, needs, situation, students’ interest, students’ ability, workshop/training, and references; (3) The teachers take part in each step of the procedure for the textbook selection. Then, they analyze and describe each component in the textbook. The teachers organize materials and the activities in each unit of the textbook based on the lesson plan they make and their students’ need. The latter, supplementary materials is designed based on the pre-existing and the objective of the lesson; and (4) the deficient time and different views among teachers are two major problems faced by the teachers when conducting textbook selection and analysis.